Array-assisted Characterization of a Fucosyltransferase Required for the Biosynthesis of Complex Core Modifications of Nematode N-Glycans - Yan, Shi (American Society for Biochemistry and Molecular Biology, 2013)
Fucose is a common monosaccharide component of cell surfaces and is involved in many biological recognition events. Therefore, definition and exploitation of the specificity of the enzymes (fucosyltransferases) involved in fucosylation is a recurrent theme in modern glycosciences. Despite various studies, the specificities of many fucosyltransferases are still unknown, so new approaches are required to study these. The model nematode Caenorhabditis elegans expresses a wide range of fucosylated glycans, including N-linked oligosaccharides with unusual complex core modifications. Up to three fucose residues can be present on the standard N,N′-diacetylchitobiose unit of these N-glycans, but only the fucosyltransferases responsible for transfer of two of these (the core α1,3-fucosyltransferase FUT-1 and the core α1,6-fucosyltransferase FUT-8) were previously characterized. By use of a glycan library in both array and solution formats, we were able to reveal that FUT-6, another C. elegans α1,3-fucosyltransferase, modifies nematode glycan cores, specifically the distal N-acetylglucosamine residue; this result is in accordance with glycomic analysis of fut-6 mutant worms. This core-modifying activity of FUT-6 in vitro and in vivo is in addition to its previously determined ability to synthesize Lewis X epitopes in vitro. A larger scale synthesis of a nematode N-glycan core in vitro using all three fucosyltransferases was performed, and the nature of the glycosidic linkages was determined by NMR. FUT-6 is probably the first eukaryotic glycosyltransferase whose specificity has been redefined with the aid of glycan microarrays and so is a paradigm for the study of other unusual glycosidic linkages in model and parasitic organisms.